Linear self-acceptance and nonlinear social comparison: interacting influences on adolescent depression - Qian-Nan Ruan; Guang-Hui Shen; Yu-Wei Wu; Dongwu Xu; Wen-Jing Yan (BMC Psychiatry)
Abstract Background This research builds on the understanding that low self-acceptance is an important feature of adolescent depression, and that social comparison is a critical factor in self-concept formation during adolescence. However, there are gaps in our understanding of their interactive effects and the non-linear features between these factors in influencing adolescent depression. Aim The study attempts to test two main hypotheses: (1) increased levels of self-acceptance will correlate with reduced depressive symptoms and moderate the negative effects of social comparison on depression; and (2) the relationship between social comparison and depression will exhibit nonlinearity at different levels of self-acceptance. Method The study involved 243 adolescents undergoing psychiatric assessment, using dyadic polynomial regression analysis and response surface analysis. These methods were used to assess linearity or nonlinearity and interaction effects between self-acceptance, social comparison and depression. Results Significant findings included a strong negative correlation between self-acceptance and depression. Self-acceptance also showed a negative correlation with social comparison. Polynomial regression revealed a non-linear relationship between social comparison and depression, with moderate levels being beneficial but excessive levels being detrimental. The interaction effect suggested that high self-acceptance might buffer the negative effects of intense social comparison. Furthermore, response surface analysis revealed complex, non-linear interactions between these variables. Conclusions This study highlights the protective role of self-acceptance against depression and the complex, non-linear effects of social comparison. It highlights the importance of promoting self-acceptance and a balanced approach to social comparison in adolescent mental health interventions.